2019
DOI: 10.1029/2019ea000664
|View full text |Cite
|
Sign up to set email alerts
|

A Relationship Between Blue and Near‐IR Global Spectral Reflectance and the Response of Global Average Reflectance to Change in Cloud Cover Observed From EPIC

Abstract: We performed a detailed analysis of Earth Polychromatic Imaging Camera (EPIC) spectral data. We found that the vector composed of blue and near‐infrared (NIR) reflectance follows a counterclockwise closed‐loop trajectory from 0 to 24 UTC as Earth rotates. This nonlinear relationship was not observed by any other satellites due to limited spatial or temporal coverage of either low Earth orbit or geostationary satellites. We found that clouds play an important role in determining the nonlinear relationship in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…We used two different MODIS products (Table 1), totaling seven optical spectral bands (i.e., blue, green, red, NIR, SWIR5, SWIR6, and SWIR7). Contrary to the case of Vegetation Indices, cloud contamination produces higher reflectance values than expected from vegetation in all spectral bands [49]. Therefore, during the preprocessing of the spectral bands coming from the Vegetation Index product (i.e., blue, red, NIR, and SWIR7), we combined the images from both satellites and created a composite, keeping pixels with the lowest values, (corresponding to the highest absorption), resulting in 23 images per band and per year.…”
Section: Preprocessingcontrasting
confidence: 69%
“…We used two different MODIS products (Table 1), totaling seven optical spectral bands (i.e., blue, green, red, NIR, SWIR5, SWIR6, and SWIR7). Contrary to the case of Vegetation Indices, cloud contamination produces higher reflectance values than expected from vegetation in all spectral bands [49]. Therefore, during the preprocessing of the spectral bands coming from the Vegetation Index product (i.e., blue, red, NIR, and SWIR7), we combined the images from both satellites and created a composite, keeping pixels with the lowest values, (corresponding to the highest absorption), resulting in 23 images per band and per year.…”
Section: Preprocessingcontrasting
confidence: 69%
“…The rainforests play a uniquely important role in carbon and water cycles across regional to global scales as it contains nearly 50% of the tropical forest carbon stocks and is the most productive and biodiverse of terrestrial ecosystems (Saatchi et al, 2011). It was found that the green vegetation contributes significantly to the NIR global average reflectance when the South America appears in the EPIC's field of view (Wen et al, 2019) suggesting a significant contribution from the equatorial forests. The left panel in Figure 9 demonstrates BRF of Amazonian forests derived from Terra MISR data acquired on August 28, 2016, at 10:30 local solar time.…”
Section: Forest Brfmentioning
confidence: 99%
“…Our research supports the idea that clouds and albedo, which ultimately determine the SW radiation, are variables of the utmost importance for current climate change, in agreement with previous research about the changes in stratocumulus or energy imbalance in the last four decades for example. An increase in cloud coverage of 0.1 would, on average, lead to a 7% increase in spectrally integrated global average reflectance of shortwave radiation 55 . The Decadal Survey for Earth Science and Applications from Space (2018) lists as one of the key science questions "how changing cloud cover and precipitation will affect climate, weather and Earth's energy balance in the future".…”
Section: Discussionmentioning
confidence: 99%